Institutional reform success indicators in higher education / Yasni Nurul Huda Mohd Yassin ... [et al.] - Mohd Yassin, Yasni Nurul Huda; Ismail, Azianti; Mohd Shaharoum, Awaluddin; Othman, Akmal Aini (Universiti Teknologi MARA, Perlis, 2021)
Reformation of higher education (HE) institutions is fundamental in improving and strengthening its academic institutions of HE independence. Moving on now to consider the present academic community must undergo a process of change to improve the teaching, research, management functions, and operations of the institutions, which are incremental in a sustainable manner. In essence, there are many indicators of success that have been identified in studies conducted for other industries. The major trend currently observed is the reformation of the HE institutions in major countries mimicking the for-profit industries to make them more competitive. This paper integrates and advances pertinent factors that enable an effective and successful reformation process from the Asian HE perspective by reviewing relevant reformation literature on the matter. This systematic review has developed three (3) core themes relating to the importance of leadership, policy development and governance, and autonomy, which regards higher institutional practices from within the Asian region reviewed. And to conclude, the internal factor is dominating the indicators for HE reforms success. This finding seeks to offer future research to be extended from established institutions from other developed countries as a comparison when planning and implementing change initiatives at the institutional level.